2001
DOI: 10.1021/bc000082g
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of a Potent, Long-Lasting Form of Interferon:  A 40 kDa Branched Polyethylene Glycol-Conjugated Interferon α-2a for the Treatment of Hepatitis C

Abstract: A potent, long-lasting form of interferon alpha-2a mono-pegylated with a 40 kilodalton branched poly(ethylene glycol) was designed, synthesized, and characterized. Mono-pegylated interferon alpha-2a was comprised of four major positional isomers involving Lys31, Lys121, Lys131, and Lys134 of interferon. The in vitro anti-viral activity of pegylated interferon alpha-2a was found to be only 7% of the original activity. In contrast, the in vivo antitumor activity was severalfold enhanced compared to interferon al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
397
2
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 587 publications
(429 citation statements)
references
References 25 publications
22
397
2
4
Order By: Relevance
“…A well-cited example is PEGylated interferon α-2a (Pegasys®, Roche, USA). The 40 kDa branched PEG conjugate retained only 7% of the antiviral activity of the native protein, but still displayed improved PK following weekly injections in vivo in hepatitis C patients [33]. In contrast, bioactivity analysis from the T47D cAMP assay indicated that the potency and efficacy of sCT-P of increasing MW compared well to native sCT, with sCT-P (40 kDa) retaining 72% of the maximum bioactivity.…”
Section: Discussionmentioning
confidence: 92%
“…A well-cited example is PEGylated interferon α-2a (Pegasys®, Roche, USA). The 40 kDa branched PEG conjugate retained only 7% of the antiviral activity of the native protein, but still displayed improved PK following weekly injections in vivo in hepatitis C patients [33]. In contrast, bioactivity analysis from the T47D cAMP assay indicated that the potency and efficacy of sCT-P of increasing MW compared well to native sCT, with sCT-P (40 kDa) retaining 72% of the maximum bioactivity.…”
Section: Discussionmentioning
confidence: 92%
“…Pegylation has been shown to improve the pharmacokinetics of proteins, polymers and small molecules (18)(19)(20)(21). Conjugation of hydrophilic PEG onto polymers hinders the adsorption of opsonins, preventing their recognition by the reticuloendothelial system (RES) (22).…”
Section: Introductionmentioning
confidence: 99%
“…The PEG-IFN-α 2b (12 kDa) is more rapidly absorbed (with an absorption half-life of 4.6 h), presents a wide volume of body distribution (approximately 0.99 L/ kg) and a mean elimination time of 40 h. However, PEG-IFN-α 2a (40 kDa) is absorbed more slowly (absorption half-life, 50 h), its distribution is restricted to well-vascularized organs with good perfusion, such as the liver, and it remains detectable in the serum for one week (approximately 65 h elimination half-life) [6,12,13].…”
Section: Pharmacological Characteristics Of the Pegylated Interferonsmentioning
confidence: 99%